Characterization of fucoxanthin triplet-state in pyridine and photoprotection in the LHC of Aureococcus anophagefferens - Trathnigg, Marco (Jihočeská univerzita, 2018)
Spectroscopic properties of the triplet state of the carotenoid fucoxanthin were studied in pyridine, thylakoid membranes and isolated light-harvesting complex of the alga Aureococcus anophagefferens. Extinction coefficient of fucoxanthin triplet absorption, and rate constant of triplet transfer from chlorophyll a to fucoxanthin in solution were estimated.
Characterization of fucoxanthin triplet-state in pyridine and photoprotection in the LHC of Aureococcus anophagefferens